Preparation of a Chemical Sensor Based on Modified Silver Nanoparticles for Quick Recognition of 5-Fluorocytosine - Gong, Wen-Jun; Dong, Cai-Xia; Chen, Jun; Zhang, Tian-Ying; Zhang, Yu-Ping; Bai, Lian-Yang (Asian Journal of Chemistry, 2012)
A chemical sensor of p-aminobenzene sulfonic acid functionalized silver nanoparticles was initially prepared, which can be used for quick recognition of 5-fluorocytosine. The presence of 5-fluorocytosine can induce the aggregation of nanoparticles due to electron donor-acceptor interaction between the target and p-aminobenzene sulfonic acid on the surface of silver nanoparticles, resulting in a shift in the surface plasmon band and a consequent colour change of the silver nanoparticles from yellow to green. Moreover, the high selectivity of p-aminobenzene sulfonic acid-modified silver nanoparticles for the target was approved with a significantly higher absorption ratio (A645/A390) compared with other seven molecules with similar structures. The concentration of 5-fluorocytosine was determined with a limit of detection lower than 0.08 mg/L by the naked eyes and the sensitivity could be enhanced by the adjustment of ion strength and pH.